PERAN TANGGUNG JAWAB DAN KENDALA NOTARIS DALAM PERUBAHAN PERUSAHAAN BERBENTUK PERSEROAN KOMANDITER MENJADI PERSEROAN TERBATAS - DIAN AFRIANI LUBIS (PREMISE LAW JURNAL, 2017)
Increasing a status to become legal entity can be done by changing CV (Limited Partnership) to PT (Corporation) so that the status of association will be automatically terminated by the law and it changes to legal entity. The establishment of PT should have the approval from the Ministry of Law and Human Rights of the Republic of Indonesia and its validity can be made by online through SABH. Some of a Notary’s obstacles are as follows: SABH cannot be accessed, there is a legal act which is not included in the PT’s statutes, RUPS does not approve of the legal act of CV to be taken over by PT, there is a fraud by its founder who has bad faith in changing the CV to PT, and the shares are owned by two persons. A Notary’s effort to handle the obstacles is that he has to be cautious and prudent in embodying legal act by the shareholders of the CV in the PT’s statutes, especially before the changing occurs, either about the agreements with the third party or about the obligations of the shareholders of the CV before the changing occurs. Keywords: Corporation, Change in a Firm, Notary’s Role